1994
DOI: 10.1093/nar/22.22.4566
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of cDNA encoding human DNA helicase Q1 Which has homology toEscherichia coliRec Q helicase and localization of the gene at chromosome 12p12

Abstract: A complementary DNA encoding DNA-dependent ATPase Q1 possessing DNA helicase activity, which is the major DNA-dependent ATPase in human cell extracts, was cloned from a cDNA library of human KB cells. The predicted amino acid sequence has seven consecutive motifs conserved in the RNA and DNA helicase super family and DNA helicase Q1 belongs to DEXH helicase family. A homology search indicated that helicase Q1 had 47% homology in the seven conserved regions with Escherichia coli RecQ protein. Three RNA bands of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
107
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 50 publications
0
107
0
1
Order By: Relevance
“…However, increased protease sensitivity in the presence of poly(U) is also seen with chymotrypsin, rendering these possibilities unlikely. Furthermore, an increase in protease sensitivity is observed with ssRNAs as small as U 20 (data not shown), which represents the approximate site size for RNA binding to eIF4A.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, increased protease sensitivity in the presence of poly(U) is also seen with chymotrypsin, rendering these possibilities unlikely. Furthermore, an increase in protease sensitivity is observed with ssRNAs as small as U 20 (data not shown), which represents the approximate site size for RNA binding to eIF4A.…”
Section: Methodsmentioning
confidence: 89%
“…RNA concentrations and thermodynamic constants involving RNA are given in 20-mer units (nucleotide concentration divided by 20), unless otherwise noted. A 20-mer is approximately the minimal site size for RNA binding to eIF4A ((14-16); Unpublished Results).…”
Section: Methodsmentioning
confidence: 99%
“…YAC ICI36ECI was the smallest YAC found to be positive for KRAG by PCR, placing this gene between STS D12S1596 and D12S1316. The human DNA helicase Q1 (RECQL) (Seki et al, 1994;Puranam, 1995), the islet amyloid polypeptide (IAPP) (Hoovers et al, 1993) and lactate dehydrogenase isoenzyme B (LDHB) genes (Li et al, 1988) were previously mapped to band 12p12. We were able to localize these genes to the distal part of our YAC contig ( Figure 1a) and their order was determined by PCR on the di erent YACs.…”
Section: Candidate Genes and Semi-quantitative (Rt ± Pcr)mentioning
confidence: 99%
“…The BLM protein has been identi®ed as a member in the DExH boxcontaining RecQ helicase subfamily (Ellis et al, 1995). Its primary sequence presents similarities with all known members in the RecQ subfamily, including Escherichia coli RecQ (Umezu et al, 1990), Saccharomyces cerevisiae Sgs1p (Ganglo et al, 1994;Watt et al, 1995), Schizosaccharomyces pombe Rqh1 (Stewart et al, 1997), Drosophila melanogaster DmBLM (Kusano et al, 1999), human RecQL (Puranam and Blackshear, 1994;Seki et al, 1994), human Wrn, the product of the Werner's syndrome gene (Yu et al, 1996) and the recently identi®ed human RecQ4 and RecQ5 proteins (Kitao et al, 1998). Chester et al (1998) developed a mouse model for the human Bloom's syndrome, and showed that mouse embryos homozygous for a targeted mutation in the murine Bloom's syndrome gene die by embryonic day 13.5, but little is known about function(s) of BLM.…”
Section: Introductionmentioning
confidence: 99%